Internalization Of Students’ Moral Values Through the Hidden Curriculum: Lickona's Perspective - Maudia, Mefta; Sarah Gunawan, Aurellia; Kamila Safithri, Najma; Hindun (Global Expert: Jurnal Bahasa dan Sastra, 2025)
This analysis investigates the implementation of the hidden curriculum and its contribution to cultivating moral values in students of the Indonesian Language and Literature Education Study Program. The research is motivated by the limited exploration of how character formation occurs outside formal instruction, particularly regarding the alignment of hidden practices with Lickona’s character education framework. The main problem addressed is the gap between the formally planned curriculum and the moral values implicitly shaped through daily interactions, institutional culture, and lecturer-student relations. This qualitative descriptive study collects data through in-depth interviews with experienced lecturers and a review of relevant literature. Findings show that the hidden curriculum significantly supports the development of moral values emphasized in Lickona’s framework, namely moral knowing, moral feeling, and moral action through modeling, classroom routines, implicit norms, and lecturers’ interpersonal approaches. More concretely, students demonstrate increased discipline, responsibility, empathy, and respect as outcomes of these hidden curricular practices. These results indicate that the hidden curriculum functions as an essential complement to the formal curriculum, contributing to students’ holistic character formation. Keywords:  Character Education, Curriculum, Hidden Curriculum, Lickona’s Framework, Moral Values